Chorioamnionitis with or without funisitis increases the risk of hypotension in very low birthweight infants on the first postnatal day but not later. Issue 5 (19th April 2006) - Lee, S Y R; Ng, D K; Fung, G P; Chow, C B; Shek, C C; Tang, P M; Shiu, Y K; Yu, V Y H
Abstract : Objective: To evaluate the relation between chorioamnionitis and hypotension in very low birthweight infants. Methods: Retrospective cohort study in infants with a birth weight of <1500 g born between January 2002 and September 2004. The placentas were examined for evidence of chorioamnionitis and funisitis. Hypotension was defined by the use of vasopressors. Results: Of 105 infants, 37 (35%) were chorioamnionitis positive. The onset of hypotension had a skewed distribution: day 1 for 30 episodes and scattered from day 2 to day 19 for the remaining 22. Of the 30 infants who developed hypotension on day 1, 17 (57%) were chorioamnionitis positive. The mean maturity of the chorioamnionitis positive group was 27.91 weeks, marginally less than the mean maturity of 29.05 weeks of the chorioamnionitis negative group (p = 0.05). After adjustment of the effects for confounding variables (birth weight, gestation, surfactant therapy, mechanical ventilation on day 1, high frequency oscillatory ventilation, patent ductus arteriosus), chorioamnionitis was the significant factor in line with hypotension developing on day 1 (adjusted odds ratio 5.14, 95% confidence interval 1.51 to 17.50). There was no evidence that hypotension developing after day 1 was associated with chorioamnionitis. Conclusions: There is a strong association between chorioamnionitis and hypotension developing on day 1 in very low birthweight infants.